2006
DOI: 10.1196/annals.1374.049
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Spotted Fever in Crete, Greece

Abstract: The clinical, epidemiological, and therapeutic aspects of 15 patients with Mediterranean spotted fever (MSF), admitted to the Internal Medicine Department of the General Hospital of Sitia (southeastern Crete, Greece) between December 2000 and July 2003, were studied. Diagnosis was made on the basis of clinical signs and symptoms and was confirmed by serology. Of the patients studied, 67% were men and 33% women, with a median age of 52 years (range of 23-76 years). Ten cases (67%) were diagnosed between May and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
2
10
1
Order By: Relevance
“…Although no ticks from Crete were PCR-positive for R. conorii [37], the bacterium was isolated from R. sanguineus and humans in other areas of Greece with high seroprevalence in people [38, 39]. More importantly, several cases of human Mediterranean spotted fever have been reported in Greece [40, 41].…”
Section: Resultsmentioning
confidence: 99%
“…Although no ticks from Crete were PCR-positive for R. conorii [37], the bacterium was isolated from R. sanguineus and humans in other areas of Greece with high seroprevalence in people [38, 39]. More importantly, several cases of human Mediterranean spotted fever have been reported in Greece [40, 41].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies (213,226,227) have confirmed that this disease is characterized by fever (94 to 100%), flu-like symptoms (78%), prostration (64%), an eschar at the tick bite site (53 to 77%), and a rash spreading to the palms and soles (87 to 96%) that is either maculopapular (94%) or petechial (6%) (Fig. 8).…”
Section: Tick-borne Rickettsiae In Europe Species Identified As Pathomentioning
confidence: 91%
“…MSF cases have been reported in Greece, and R. conorii has been isolated both from patients and ticks [5][6][7][8][9]. However, the disease is likely to be underestimated in this country and diagnosis is based mainly on clinical symptoms or only on serology.…”
Section: Introductionmentioning
confidence: 99%